2021
DOI: 10.1111/hsc.13338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nature and impact of occupational stress on Australian rural aged care workers

Abstract: This study explored the nature and impact of occupational stress on direct-care workers employed by aged care providers in rural Australia. The Job demands-Resources (JD-R) model of occupational stress provided the theoretical framework to guide this qualitative investigation. A series of four FGs were conducted with direct-care workers (n = 23), who reported their job demands, job resources and personal resources. Direct-care workers identified six themes related to job demands: time pressure, physical demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Once employed in a role, people with dyslexia face a myriad of challenges trying to keep up with workplace demands, particularly when their disability was unsupported. Similar to local [ 70 , 71 , 72 , 73 , 74 , 75 ] and international research [ 39 , 40 , 41 , 63 , 76 ] that has used the JD-R Model we also found that when employees are faced with high job demands and low job resources that they can face high levels of job burnout. However, we could not determine whether those with dyslexia faced additional job burnout because of their disability compared to the general population, or differences in job burnout based on specific industries.…”
Section: Discussionsupporting
confidence: 72%
“…Once employed in a role, people with dyslexia face a myriad of challenges trying to keep up with workplace demands, particularly when their disability was unsupported. Similar to local [ 70 , 71 , 72 , 73 , 74 , 75 ] and international research [ 39 , 40 , 41 , 63 , 76 ] that has used the JD-R Model we also found that when employees are faced with high job demands and low job resources that they can face high levels of job burnout. However, we could not determine whether those with dyslexia faced additional job burnout because of their disability compared to the general population, or differences in job burnout based on specific industries.…”
Section: Discussionsupporting
confidence: 72%
“…12 Prior to COVID-19 Australian aged care workers reported work-related demands that focused primarily on the tasks involved in their roles such as time pressure, physical demands, administrative requirements, insufficient staff mix and training to deal with complex conditions and work scheduling. 13 Clearly COVID-19 has intensified these taskrelated demands and added additional emotional demands including complicated grief and loss.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported here further add to the qualitative research on the JD-R model with a new focus on the current pandemic environment. 6,13 Nuanced examples have been provided that describe the complexity of emotional demands of grief and loss associated with psychological adjustment of caring for people with COVID as well as their estranged family members (unable to visit due to restrictions) and during their end of life. These were shown to be overwhelming with serious health implications such as lengthy work absences.…”
Section: Discussionmentioning
confidence: 99%
“…Providing access to ongoing training has been considered to be a positive organizational value in this sector, although funding constraints have been noted as a reason for less frequent training days, with training moving towards online modules or short presentations [3]. Aged care staff that feel well supported with regular training feel motivated and training assists with the development of skills [29]. Aged care providers need to ensure that there is strong leadership driving change within aged care homes at the systems level, which would be further supported by food and nutrition champions.…”
Section: Discussionmentioning
confidence: 99%